PSO-based Optimal PID Controller for Twin Rotor MIMO System - Marie, Mehdi J.; AL-Suhai, Ghaida A.; Latif, Wisam A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Optimum design methods based on soft computing have proved their excellence in industrial automatic control systems. In this paper, a proposed system is presented to treat the tuning of proportional, integral and derivative (PID) controller parameters to control the behavior of the Twin Rotor Multi-Input-Multi-Output (MIMO) System (TRMS). The system can be decoupled into two paths the main and the tail. The use of Particle Swarm Optimization (PSO) algorithm for tuning the controller parameters aims to get a stable control system. The simulation results reveal significant improvements in the step response characteristic such as reducing the steady state error, rise time, settling time and the number of overshoots in position control of the TRMS. Thus, the PSO based PID controller in this system proves better performance compared to the traditional existing PID one.